2008
DOI: 10.1080/15287390801988160
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Squamous-Cell Cancer and its Association with Polymorphic Enzymes of Xenobiotic Metabolism and Repair

Abstract: Tobacco smoking, alcohol drinking, and occupational exposures to polycyclic aromatic hydrocarbons are the major proven risk factors for human head and neck squamous-cell cancer (HNSCC). Major research focus on gene-environment interactions concerning HNSCC has been on genes encoding enzymes of metabolism for tobacco smoke constituents and repair enzymes. To investigate the role of genetically determined individual predispositions in enzymes of xenobiotic metabolism and in repair enzymes under the exogenous ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 38 publications
4
54
2
2
Order By: Relevance
“…A total of 45 abstracts were retrieved through PubMed and Medline, and 2 additional articles were found through the ISI Web of Knowledge. After reviewing all 47 articles carefully, 16 eligible articles including 2,965 cases with HNC and 3,919 controls were identified and included in the final meta-analysis (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The main characteristics of all 16 studies are described in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 45 abstracts were retrieved through PubMed and Medline, and 2 additional articles were found through the ISI Web of Knowledge. After reviewing all 47 articles carefully, 16 eligible articles including 2,965 cases with HNC and 3,919 controls were identified and included in the final meta-analysis (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The main characteristics of all 16 studies are described in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…They observed that carrying the XPD (Lys 751 Gln), Gln/Gln genotype was associated with HNSCC (OR=0.54; 95% CI = 0.35-0.92; P = 0.006) [44]. In another case-control study conducted by Harth et al [13] on 312 cases and 300 controls, the XPD (Lys 751 Gln) C/C genotype and combined XPD (Arg 156 Arg) C/A and A/A genotypes were predominant in HNSCC patients [13]. In a non-Hispanic white population, Sturgis et al [11] reported XPD (Lys 751 Gln, rs13181) gene polymorphism to have significant positive association with HNSCC risk [11].…”
Section: Nucleotide Excision Repair (Ner)mentioning
confidence: 99%
“…At the cellular and tissue level, these biological responses become modified by exogenous and endogenous compounds due to the occurrence of polymorphic alleles in DNA repair genes that alter the repair capacity, thereby developing different kinds of diseases, such as cancer [17]. The polymorphic DNA repair genes involved in HNSCC are grouped into four major DNA repair pathways: Base excision repair (BER), nucleotide excision repair (NER), double-strand DNA breaks repair (DSBR) and mismatch repair (MMR) [12][13][14].…”
Section: Genetic Polymorphisms With Impact On Dna Damage and Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentre elas destacam-se as CYP1A1 e CYP2E1. (Harth et al, 2008;Cury et al, 2012;Waters et al, 2010).…”
Section: Biomarcadores De Efeitounclassified